Savvy viewers and (simulated) reality TV: An analysis of The Bachelor's appeal to viewers. Issue 1 (1st March 2020) - Church, Scott Haden; Robinson, Tom; Callahan, Clark; Klotzer Barboza, Katherine; Montez, Daniel
The reality television programme The Bachelor (2002‐present) has received a large amount of academic attention since it premiered on ABC in 2002. The majority of that literature approaches the show critically to address issues relating to the representation of race, gender, consumerism, identity and relationships within the format of a competition. Other research on the show ruminates about its relationship to its 'savvy' viewers who know reality television is not truly real and yet paradoxically continue to be highly invested in the outcome of its shows. Yet other literature probes for the gratifications embedded in the viewing process and the perceptions of dating that the show cultivates in its viewers. The longevity of The Bachelor can be attributed to the sense of allegiance the viewers feel to the show. To that end, this study is an inquiry into perceptions of the show by its viewers. Using the Q sort methodology, this empirical study reveals insights into its appeal by providing clearly grouped audiences and their particular uses for the show. It also addresses the interface between reality television, social media and the mediated representation of romantic relationships.